The high-temperature superionic behaviour of Ag(2)S - Hull, S; Keen, D; Sivia, D; Madden, P; Wilson, M (2002)
Powder neutron diffraction and molecular dynamics (MD) simulations have been used to investigate the structural behaviour of silver sulfide, Ag2S, at elevated temperatures. Above ∼450 K Ag2S adopts the β phase in which the S2- posses a body-centred cubic arrangement. Analysis of the neutron diffraction is in good agreement with the previously proposed structural model in which the Ag+ predominantly reside within the tetrahedral interstices. At ∼865 K Ag2S transforms to the α phase in which the anion sublattice adopts a face-centred cubic arrangement. Structural refinements of this phase indicate that the cations are distributed predominantly in the tetrahedral cavities but with a significant fraction in the octahedral holes. MD simulations, using established potentials for this compound, confirm the stability of the two high-temperature superionic phases and show good agreement with the measured Ag+ distribution within the unit cell.